Guilty Pleasures : Popular Novels and American Audiences in the Long Nineteenth Century - McIntosh, Hugh, 1978- (Book collections on Project MUSE., 2018)
"Examining reactions to bestselling fiction in America from 1850-1920, the period in which popular novels became national phenomena, Guilty Pleasures argues that ambivalence about public taste sparked a wide-ranging exploration of individualism and national identity"--